REGISTRATION OF SURFACE ACOUSTIC WAVES in Z-SECTIONS of PIEZOELECTRIC SINGLE CRYSTALS ZnO and CdS - I. V. Linchevsky; M. V. Chursanova (Radio Physics and Radio Astronomy)
Subject and Purpose. The subjects of this research are the internal electric field and the electric polarization vector, both existing in the volume of a deformed piezoelectric crystal. The work has been aimed at determining the dynamic electric polarization within the Z-section of a class 6 mm piezoelectric single crystal, deformed by surface acoustic waves (SAW), and estimating the sensitivity of the electrode pair of the inter-digit transducer in the mode of recording surface acoustic waves in Z-sections of the piezoelectric crystals.